Effect of chemical and mechanical weed control on weed seed banks in rice field - Umiyati, Uum; Widayat, Dedi; Maharani, Yani (Universitas Padjadjaran, 2024)
Weed control is essential for ensuring the diversity of weeds on agricultural land. A study was conducted in rice fields in Subang and Cianjur districts, where 24 fields were observed to have varying weed management approaches. The research employed descriptive methods, including surveys to identify weed types and destructive methods to analyze weed seed banks at different depths. The descriptive methods included surveys to identify weed types and destructive methods to analyze weed seed banks at different depths. Each district contained twelve rice fields that reflected diverse environmental conditions and weed control techniques, yet shared a similar age range of 1-5 weeks. The study examined the weed vegetation, community coefficients, weed diversity, weed dominance, and variations in seed banks at various depths. The results indicated that fields without herbicide-based weed control had a higher number of weed species than those using herbicides. Herbicide use effectively decreased weed populations, subsequently altering the seed bank composition. The dominant weeds in herbicide-treated fields were Cynodon dactylon, Pistia stratiotes, and Ludwigia adscendens, whereas Ludwigia adscendens, Cynodon dactylon, and Pistia stratiotes were dominant in fields without herbicides.